Methionine requirement of milkfish (Chanos chanos Forsskal) juveniles - Sastrillo, Mary Agnes S. (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1990)
Methionine requirement of milkfish at two dietary cysteine levels was investigated using a 5x 2 factorial feeding experiment. The basal diet containing 36% protein composed primarily of soybean protein concentrate and free amino acids was supplemented with crystalline L-methionine so that dietary concentrations were 0.24, 0.54, 0.84, 1.14, and 1.44% and L-cystine to make dietary levels at 0.28 and 1.48 %.Milkfish juveniles with an average size of 0.21 g were stocked in 60-L rectangular glass tanks provided with recirculating water and fed the experimental diets for 12 weeks. A practical diet was formulated to compare growth of fish with the amino acid test diets. Breakpoint linear regression analysis of the growth data estimated methionine requirement at 0.98% of the diet (2.7% of protein) at 0.28% dietary cysteine. In the presence of 1.48% cysteine, methionine requirement was estimated at 0.54% (1.5% of protein) suggesting that cysteine reduced the dietary requirement for methionine. Significantly higher weight gain (P<0.05) was obtained when fish were fed higher dietary cysteine level (1.48%) at all levels of methionine than when fed diets with 0.28% cysteine. This suggests that methionine cannot completely replace cysteine. Growth of fish fed practical diet was significantly higher than the growth of fish fed amino acid test diets (P<0.01). No significant difference in survival and feed conversion ratio was observed among test diets and practical diet. Depression in growth of milkfish was observed when fish were fed 1.44% dietary methionine (4.0% of protein), regardless of dietary cysteine level, suggesting toxicity at this level of methionine. Eye cataract was not detected in fish fed methionine deficient diets after twelve weeks of feeding.
Thesis (M. S. Fisheries-Aquaculture) -- Miagao, Iloilo : University of the Philippines in the Visayas, March 1990.
Keywords: Milkfish; Chanos chanos Forsskal; Methionine; Juveniles